2020
DOI: 10.1016/j.mehy.2020.110155
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ABO blood groups on COVID-19 susceptibility and severity: A molecular hypothesis based on carbohydrate-carbohydrate interactions

Abstract: The world is experiencing one of the most difficult moments in history with the COVID-19 pandemic, a disease caused by SARS-CoV-2, a new type of coronavirus. Virus infectivity is mediated by the binding of Spike transmembrane glycoprotein to specific protein receptors present on cell host surface. Spike is a homotrimer that emerges from the virion, each monomer containing two subunits named S1 and S2, which are related to cell recognition and membrane fusion, respectively. S1 is subdivided in domains S1A (or N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 103 publications
0
59
0
3
Order By: Relevance
“…Although some inconsistent results have been reported, most studies agree that ABO blood groups are of particular significance with regard to their association with susceptibility to COVID-19, but the molecular mechanism underlying this association has not been well described. It has been hypothesized that the blood group impact on susceptibility to COVID-19 may depend on a differential clustering of the virus glycoprotein receptors on host cell surface, induced by ABO(H) determinants through interactions (carbohydrate-carbohydrate) with the glycan motif of these receptors, and this may interfere with the binding of virus and its entrance to target cells [40]. The carbohydrate structures of ABO(H) blood groups are not restricted to the surface of red blood cells, and other cells and tissues express these structures; for instance, lymphocytes, endothelial cells, platelets, gastric mucosa and bone marrow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some inconsistent results have been reported, most studies agree that ABO blood groups are of particular significance with regard to their association with susceptibility to COVID-19, but the molecular mechanism underlying this association has not been well described. It has been hypothesized that the blood group impact on susceptibility to COVID-19 may depend on a differential clustering of the virus glycoprotein receptors on host cell surface, induced by ABO(H) determinants through interactions (carbohydrate-carbohydrate) with the glycan motif of these receptors, and this may interfere with the binding of virus and its entrance to target cells [40]. The carbohydrate structures of ABO(H) blood groups are not restricted to the surface of red blood cells, and other cells and tissues express these structures; for instance, lymphocytes, endothelial cells, platelets, gastric mucosa and bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to COVID-19, group A has been associated with severe malaria, while individuals with group O are less susceptible to the infection. Further, group A individuals are more likely to have debilitated aging than those of group O [40].…”
Section: Discussionmentioning
confidence: 99%
“…For example, blood types A and AB predispose subjects to aggravated malaria, while type O causes resistance to several protozoal infections. Furthermore, this blood grouping system exhibit direct or indirect association with some cardiovascular conditions [10]. Recently, Groot et al reported that people with A, B, and AB blood types are more susceptible to thrombosis and myocardial infarction, while those bearing the O blood group are more prone to hypertension [11].…”
Section: Introductionmentioning
confidence: 99%
“…This enticed the attention of researchers in devising therapeutic strategies to curtail the virus infection [ 41 , 64 ]. Additionally, it has also been reported that infectious SARS virions harness host histo-blood group antigens on S proteins [ 65 ], which might presumably modulate the interaction with host cell glycoprotein receptors through carbohydrate–carbohydrate interactions [ 66 ]. The current transcriptomic based research analysis is aimed to generate a hypothetical view of the alteration in glycan machinery, which could be used to explain the relevance of glycosylation underlying the lung pathology and immune responses reported in COVID-19 subjects.…”
Section: Discussionmentioning
confidence: 99%